(untitled) (American Journal of Business Management, Economics and Banking, 2023)
Most of the economic (service) entities that operate in the Iraqi environment depend on traditional methods in the process of evaluating their performance, if these methods do not give a clear and comprehensive picture of the performance of these entities because these methods are based on financial measures only, which requires the need to use one of the accounting techniques The administrative balance, which is the balanced scorecard as a modern tool for evaluating performance and giving a clear and comprehensive picture of the performance of service entities by relying on financial and non-financial measures. Therefore, the research aims to study and analyze the role of the balanced scorecard in evaluating the performance of the Directorate of Civil Defense / Muthanna through the application of this technique in its perspectives. The four through visits and field experiences in the district and relying on the Directorate’s data for the years (2018) and (2019), as well as a questionnaire form that the researchers designed and distributed to a random sample of the governorate’s residents for the purpose of analyzing their opinions about the extent of their satisfaction with the performance of the Directorate, the research sample. What the research found The application of the balanced scorecard with its four perspectives in the Directorate of Civil Defense / Muthanna Governorate (research sample) contributed to measuring and evaluating the directorate’s performance from the financial and non-financial terms, in a clear and comprehensive manner, as it was found that there was an improvement in performance for the year 2019 over the year 2018 according to the financial perspective, and that There is a great agreement about the satisfaction of the people of the province with the performance of the Civil Defense Directorate and their dedication to their duties in accordance with the perspective of learning and growth based on the outcomes of the questionnaire and the SPSS program, while there was a clear decrease in performance in 2019 compared to the performance in 2018 according to the internal operations perspective. The performance is equal for the years 2018 and 2019 according to the learning and growth perspective